Peningkatan Pemahaman Konsep Fisika Dasar Melalui Konflik Kognitif dengan Pertanyaan Tak Terduga - Muhammad Zuhdi; Muh. Makhrus (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2020)
Inter-semester courses (KAS) Classes are identical to low grade classes with students whose level of understanding is inadequate. Students in this class usually have a misunderstanding of many concepts or misconceptions. Efforts that can be performed to improve the studentÃ¢â¬â¢s concepts is the method of conceptual change through unexpected questions, namely questions that most likely have not been thought of by students or the answers have not been thought of before by the student. The aim of this study is to determine the effectiveness of conceptual change learning with unexpected questions to improve understanding of concepts. This research was conducted in the inter-semester course class of 2018-2019 school year which was conducted in July 2019, with students from all study programs at the Department of Mathematics and Natural Sciences Education, Teaching and Education Faculty, at A University in Mataram City. The results of this study indicate that this method can significantly improve understanding of the concept. The treatment has successfully increasing the understanding of concept from 26.4% to 62.9%.